THE FUTURE CONTINUOUS TENSE: A COMPREHENSIVE ANALYSIS OF FORM, FUNCTION, AND USAGE - Asatullayeva Mohinur (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The future continuous tense, also known as the future progressive tense, is a grammatical construct used to describe actions that will be in progress at a specific point in the future. This paper provides a comprehensive analysis of the future continuous tense, encompassing its formation, diverse functions, and nuanced usage within various contexts. The study explores the structural components of the tense, its role in expressing ongoing actions, predicting events, and making polite inquiries. Furthermore, the paper examines the future continuous in conjunction with other tenses, such as the simple future, to illustrate its significance in creating temporal contrasts and expressing nuanced future scenarios. The paper also delves into common errors and difficulties encountered by English language learners, and offers pedagogical implications for effective teaching and learning of the future continuous tense.